Strategies to Improve Teacher Professionalism Through The Implementation of Knowledge Management - Abdurokhim ABDUROKHIM; Syamsu Yusuf LN (International Journal of Environmental, Sustainability, and Social Science, 2021)
Teacher professionalism is closely related to those who have special skills and abilities in the field of education to optimize their duties and functions as teachers to meet the needs of the profession. This research method uses a qualitative description. The subject of this study is a certified teacher, and improves the skills of teachers by implementing knowledge management. This study focuses on teacher certification in private high schools in Cirebon Regency from 91 private high schools in Cirebon whose teachers are certified with a sample of 33 schools randomly but proportionally by region. The application of knowledge management to improve the professionalism of private teachers with madrasa certification in Cirebon Regency can be done by managing certified teacher staff through education and training. In addition, it is necessary to form a separate community to bring together certification teachers at certain times to discuss or share information and knowledge related to becoming professional teachers. The ability to use information technology is also needed to improve the pedagogic skills of certified teachers, especially in private madrasah in Cirebon Regency. The knowledge management skills of every certified teacher in private madrasas in Cirebon Regency must also be utilized in the form of sharing applications with other certified teachers. The aim is to provide insight for teachers of private Madrasah Law certification in Cirebon Regency.